Quantum nucleation of cavities in a liquid helium at low temperatures - Burmistrov, S.N.; Dubovskii, L.B. (Физика низких температур, 1997)
The rate of the quantum cavitation in normal fluid ³He and superfluid ⁴He at temperatures down to absolute zero has been studied. The effect of energy dissipation due to viscosity and the effect of the finite compressibility of a fluid are incorporated into the calculation of the quantum cavitation rate. Because of the dissipative processes, the kinetics of the quantum cavitation in ³He and ⁴He proves to be qualitatively different. In normal ³He it corresponds to the dissipative tunneling through a potential barrier. In contrast, in superfluid ⁴He the effect of dissipation is of minor importance. In both liquids the role of the compressibility of a fluid enhances significantly for the small critical nuclei, which have several interatomic distances and can provide us the nucleation rates sufficient for the experimental observation of the homogeneous cavitation in the quantum regime.